2014
DOI: 10.4238/2014.january.24.12
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lipopolysaccharide on the stearoyl-coenzyme A desaturase mRNA level in bovine primary hepatic cells

Abstract: ABSTRACT. This study aimed to compare the effects of lipopolysaccharide (LPS) on stearoyl-coenzyme A desaturase (SCD) gene expression in mouse primary hepatic cells. To obtain sufficient total RNA, primary hepatic cells were plated on 6-cm diameter-type collagen 1-coated dishes (1 x 10 6 cells per dish). The test was divided into 6 groups with 6 replications per group. The 6 groups were treated with the following volumes of LPS (0.1 mg/mL): 0, 1, 1.5, 2, 4, and 8 µL. The cells were cultured for 24 h, and the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Previous studies demonstrated that LPSs stimulate the gene expression of fatty acid synthetase (FAS) and acetyl-CoA carboxylase (ACC) in the liver of mice [ 5 ] but depressed stearoyl-CoA desaturase (SCD) expression in bovine hepatocytes [ 6 ]. SCD is a rate-limiting enzyme that catalyzes the synthesis of the monounsaturated fatty acids oleate (18:1) and palmitoleate (16:1) and forms triglycerides and cholesterol esters [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated that LPSs stimulate the gene expression of fatty acid synthetase (FAS) and acetyl-CoA carboxylase (ACC) in the liver of mice [ 5 ] but depressed stearoyl-CoA desaturase (SCD) expression in bovine hepatocytes [ 6 ]. SCD is a rate-limiting enzyme that catalyzes the synthesis of the monounsaturated fatty acids oleate (18:1) and palmitoleate (16:1) and forms triglycerides and cholesterol esters [ 7 ].…”
Section: Introductionmentioning
confidence: 99%